Effect of cubebin against streptozotocin-induced diabetic nephropathy rats via inhibition TNF-α/NF-κB/TGF-β: in vivo and in silico study - Rahamat Unissa Syed; Sivakumar S. Moni; Weiam Hussein; Taghreed Mohammad Saad Alhaidan; Sondos Mohammed Y. Abumilha; Lama Khalid Alnahdi; Ling Shing Wong; Vetriselvan Subramaniyan; Vinoth Kumarasamy (Scientific Reports)
Abstract Cubebin, a dibenzyl butyrolactone lignan belonging to several distinct families, including Aristolochiaceae, Myristicaceae, Piperaceae, and Rutaceae, and possesses several pharmacological activities, including analgesic, anti-inflammatory, antioxidant, and vasodilatory. The current study aimed to evaluate the effect of cubebin on streptozotocin (STZ)-evoked diabetic nephropathy (DN). DN is a well-identified complication of diabetes mellitus (DM) characterized by renal hypertrophy that progressively declines kidney function. Wistar rats were randomly divided into groups- normal, STZ control (65 mg/kg/body weight), and STZ + cubebin (10 and 20 mg/kg). Biochemical parameters such as glucose levels, kidney parameters, lipid profile, oxidative stress, endogenous antioxidant markers, inflammatory cytokines and histopathology were performed. Molecular docking [(PDB ID: TNF-α (7JRA), NF-κB (1SVC), TGF-β1 (3TZM)] and dynamic simulation (MDS) were also performed with the selected target. STZ-induced DN was changes in these parameters. In contrast, DN + cubebin at 10 and 20 mg/kg doses improved the biochemical parameters and histological changes. Furthermore, molecular docking and simulation studies showed a binding affinity with negative binding energy with TNF-α (7jra, − 11.342 kcal/mol), TGF-β1 (3tzm, − 9.162 kcal/mol) and NF-κB (1svc, − 6.665 kcal/mol). The results of MDS provided insight into the mechanisms that associate proteins TNF-α, NF-κB, and TGF-β1 in conformational dynamics upon binding to cubebin. In conclusion, these findings exhibit a potential effect of cubebin in STZ-evoked DN rats.